1979
DOI: 10.1149/1.2129171
|View full text |Cite
|
Sign up to set email alerts
|

The Deposition of Silicon Dioxide Films at Reduced Pressure

Abstract: Films of silicon dioxide have been deposited on silicon substrates by decomposing tetraethoxysilane (TEOS) at 700~176 in a reduced pressure CVD reactor. The deposition rate is 200-300 A/min. The thickness uniformity is better than _1% over a deposition zone capable of holding 100 wafers. The step coverage is conformal, the defect density is very low, and the film stress is compressive and low. The refractive index, infrared spectrum, and film density appear normal for deposited silicon dioxide. The addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(60 citation statements)
references
References 1 publication
7
53
0
Order By: Relevance
“…Huppertz and Engl (7) modeled the SiO2 deposition from TEOS but neglected the convective mass transport. Moreover, their kinetic model does not agree well with published data in the literature (3,4). Recently Desu (8) has shown that in the kinetics of TEOS, gas-phase decomposition is the rate controlling step.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Huppertz and Engl (7) modeled the SiO2 deposition from TEOS but neglected the convective mass transport. Moreover, their kinetic model does not agree well with published data in the literature (3,4). Recently Desu (8) has shown that in the kinetics of TEOS, gas-phase decomposition is the rate controlling step.…”
mentioning
confidence: 85%
“…There have been a number of experimental studies on the deposition of SiO2 from TEOS (2)(3)(4)(5)(6)(7)(8). It has been shown repeatedly that high quality SiO= films can be obtained from this process.…”
mentioning
confidence: 99%
“…TEOS pyrolysis has been utilized for a long time to deposit rather conformal oxide 5,9,10 at high temperatures such as 700°C. The higher deposition temperature regime is not suitable for interlayer dielectric applications.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, C 60 is usually deposited onto a thermally oxidized tunneling oxide O. Senftleben et al/C 60 Nanostructures for Applications and is then covered by deposition of a control oxide on top. This can either be done by PECVD [22,23] , by CVD growth of amorphous silicon and subsequent thermal oxidation [24,25] , by co-evaporation of silicon in an oxygen ambient [26,27] or by a low pressure chemical vapor deoposition (LPCVD) process using, e.g., tetraetoxysilane (TEOS) as a precursor [28,29] , which requires a high thermal budget of around 700 8C. The stability and the desorption behavior of C 60 in oxygen atmosphere under elevated temperatures is, therefore, of high interest.…”
Section: Inside An Amorphous Silicon Dioxide Matrixmentioning
confidence: 99%